Determinants of life satisfaction in adolescents with congenital or acquired heart disease: a nationwide cross-sectional study - Mohamad El-Chouli; Sidsel Marie Bernt Jørgensen; Daniel Mølager Christensen; Isabella Drachmann; Thomas Steen Gyldenstierne Sehested; Morten Winther Malmborg; Sandra Chamat-Hedemand; Caroline Sindet-Pedersen; Lars Idorn; Gunnar Hilmar Gislason; Thomas Alexander Gerds; Susan Ishøy Michelsen; et al. (BMC, 2024)
Abstract Background We aimed to investigate how self-reported physical and cognitive limitations (challenges), self-efficacy, and social support interacted with life satisfaction in adolescents and young adults with congenital heart disease (CHD) or acquired heart disease, among whom life satisfaction may be impaired. Methods "Adolescence with Heart Disease" was a cross-sectional, nationwide survey of patients with CHD or early acquired heart disease aged 15-25. Structural equation modeling was used to test the implied latent variable mediation model between the main outcome of interest (life satisfaction) and challenges, social support, and self-efficacy. The correlation factors between life satisfaction and the latent variables with 95% confidence intervals (CIs) were calculated. Results A total of 1691 patients were included: 72% had CHD, 52% were females, the median age at response was 20 years [interquartile range: 18;23], and 69% reported high life satisfaction. In the univariate models, high life satisfaction was significantly associated with low challenges (-0.5 [CI: -0.6;-0.5]), high self-efficacy (0.8 [CI: 0.7; 0.8]), and high social support (0.4 [CI: 0.3; 0.5]). In the multivariate model, only self-efficacy remained significantly associated with life satisfaction (0.8 [CI: 0.7; 0.9]). Furthermore, there was a significant negative covariance between challenges and both self-efficacy (-0.67) and social support (-0.4), while the two latter variables had a positive covariance (0.55). Conclusions In adolescents with heart disease, high life satisfaction was associated with high levels of self-efficacy. High levels of self-efficacy and social support attenuated the association between physical and cognitive challenges and life satisfaction. In this group that may face higher challenges than their peers, future interventions should aim to increase their self-efficacy to improve their life satisfaction, potentially through promoting social support.